The effect of aerobic exercises accompanying music on the development of some motor abilities of non-athletes women (Journal of the College of Basic Education, 2023)
The importance of this research stands out in following a new method in developing some of the motor capabilities of the research sample through the use of aerobic exercises accompanying music to form a base that serves their physical performance. This problem is worthy of study and research. The research sample included some female employees of the Technological University at the ages of (30_39) years, and they were chosen by the intentional method. The researcher recommended the need for physical education teachers to introduce training and development courses in physical education